Получение и применение наночастиц, содержащих медь и серебро - Лопатько, К.Г.; Афтандилянц, Е.Г.; Зауличный, Я.В.; Карпець, М.В. (Электрические контакты и электроды, 2010)
Приведены результаты исследования структуры и свойств наночастиц, полученных в процессе электроискровой обработки меди и серебра. Показано влияние мощности электроискрового разряда на изменение химического состава наночастиц. Методом рентгеновской фотоэлектронной спектроскопии исследован химический состав поверхности наночастиц. Приведены примеры применения наночастиц. Наведено результати дослідження структури та властивостей наночастинок, отриманих в процесі електроіскрової обробці міді та срібла. Показано вплив потужності електроіскрового розряду на зміну хімічного складу наночастинок. Методом рентгенівської фотоелектронної спектроскопії досліджено хімічний склад поверхні наночастинок. Наведено приклади застосування наночастинок. Results of research of structure and properties of nanoparticles, which received by electrospark treatment of copper and silver are shown. Influence of electrical discharge power to chemical composition of nanoparticles is also presented. Сhemical composition of nanoparticle surfaces was investigated by the method of X-ray photoelectronic spectroscopy. It was discovered that oxygen is present on nanoparticle surfaces. Nanoparticles consist of Cu2O, which appear at initial stage of synthesis and, possibly, become places for copper, oxides of CuO, molecules of Н2О and hydroxyl-group of ОН- adsorption. Layers of CuO, molecules of Н2О and anions of ОН- are removed from the nanoparticle surfaces at heating of dispersible phases up to 120—180 ºC. To decrease silver nanoparticle surface oxidization, its colloidal solutions must be synthesized at minimum water temperature (near 0 ºC). Peak discharge power reduction may also provide similar result. Examples of nanoparticles application are shown.